Fibroblastic meningioma mimicking an intracerebral hemorrhage : case report (2020)
A 50-year-old woman presented to the emergency room complaining of severe headache. A non-contrasted head CT was obtained, which demonstrated a hyperdense image compatible with an intracerebral hemorrhage in the posterior region of the left temporal lobe.